Programa de cidadania: o impacto da Nota Paraná sobre a arrecadação do ICMS no estado - Andrade, James Vanin de (2019)
Even though governments play a prevailing role on collectivity’s management, it is the effective citizen´s participation that determines, ultimately, people´s life quality. Aiming to increase individual´s perception of its own role within social structure, various governments adopt citizenship programs. Studies on programs impacts in Brazil have analyzed such programs under distinct perspectives and, amongst them, they have measured tax collection increase as an outcome of such programs. Such studies lack results on segregated economic sectors. It is important that public managers can know which sector play a more significant result on tax collection in order to optimize them. In this trail, this study evaluated the impact of Nota Paraná´s citizenship program on ICMS tax collection within the eleven biggest retail sectors after its implementation in 2015. Data form the two previous years and three years after program´s creation were used in order to evaluate the tax collection impact on each selected economic sector. Even though the method was more suited to inform global tax collection increase due to the citizenship program, segmented analysis showed statistic relevance for seven amongst the eleven analyzed sectors. Results grant a better understanding of the program in quantitative perspective, and obtaining a panoramic view of results distribution on various economic segments, opening way for other researchers to find new approaches that will allow citizenship programs in various states and countries to evolve.